BioModels’ Model of the Year 2023 - Malik Sheriff, Rahuman S.; Asari, Hiroki; Hermjakob, Henning; Huber, Wolfgang; Quail, Thomas; Santos, Silvia D. M.; Smith, Amber M.; Uhlmann, Virginie (Frontiers in Systems Biology, 2024)
Mathematical modeling is a pivotal tool for deciphering the complexities of biological systems and their control mechanisms, providing substantial benefits for industrial applications and answering relevant biological questions. BioModels’ Model of the Year 2023 competition was established to recognize and highlight exciting modeling-based research in the life sciences, particularly by non-independent early-career researchers. It further aims to endorse reproducibility and FAIR principles of model sharing among these researchers. We here delineate the competition’s criteria for participation and selection, introduce the award recipients, and provide an overview of their contributions. Their models provide crucial insights into cell division regulation, protein stability, and cell fate determination, illustrating the role of mathematical modeling in advancing biological research.